The trend of research on oral hygiene in intubated patient based on bibliometric analysis - Titis Wening Setyoharsih; Saryono Saryono; Latifah Jehloh (Jurnal Keperawatan Padjadjaran, 2024)
Background: ICU patients with critical conditions are generally intubated due to their inability to breathe independently. These patients require assistance from nurses in meeting their basic needs, one of which is oral hygiene. ICU nurses use several protocols when doing oral hygiene in intubated patients. Purpose: This study was conducted to reveal the trend of research on oral hygiene in intubated patients in the last two decades through bibliometric analysis. Methods: This study is a quantitative research. The research publications were collected from the Scopus and PubMed databases through the Publish or Perish application. Then, for further analysis, the VOSViewer application was used to create visualization maps of co-occurring terms that include the research themes. Results: There were a total of 88 publications from two databases in the last two decades that discussed oral hygiene in intubated patients. Visualization in VOSViewer illustrates five main clusters on oral hygiene-intubated patients. Most of the publication themes were oral hygiene protocols and the relationship between the oral hygiene and VAP incidence. However, suction toothbrush as one of the oral hygiene protocol did not appear in the co-occurring terms in the first search; therefore, the researchers conducted a separate search about this term. Conclusions: Based on the analysis, the most common themes used are oral hygiene protocols and the relationship between oral hygiene and VAP in the last two decades. However, research on suction toothbrush as one of the protocols is still lacking, so it can be used as a novelty in conducting further research.